2010
DOI: 10.2519/jospt.2010.3224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recovery Method After Exercise on Performance, Immune Changes, and Psychological Outcomes

Abstract: A widespread belief among many coaches and athletes is that relatively large volumes of intense training must be performed to maximize gains in pera common training model used by coaches and athletes is based on the "overload principle" or "physical stress theory." 14 An essential component of the model is that high-intensity physical exercise creates a disturbance in cellular homeostasis. This disturbance then acts as a stimulus that initiates physiological responses to restore homeostasis and induce training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 46 publications
3
28
0
4
Order By: Relevance
“…These Wndings are in accordance with previous research on recreational subjects utilising CWT (CoVey et al 2004;Versey et al 2010) or CWI (Stacey et al 2010) therapy following similar exercise intensities and/or bouts. To the best of the authors knowledge, no previous research uses a subject population of such international (elite) calibre, and accordingly, where the highly trained status of the subject population may predispose them to a faster recovery than untrained populations (Ravier et al 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These Wndings are in accordance with previous research on recreational subjects utilising CWT (CoVey et al 2004;Versey et al 2010) or CWI (Stacey et al 2010) therapy following similar exercise intensities and/or bouts. To the best of the authors knowledge, no previous research uses a subject population of such international (elite) calibre, and accordingly, where the highly trained status of the subject population may predispose them to a faster recovery than untrained populations (Ravier et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the lower CK concentrations via the reduction of cellular, lymphatic and capillary permeability may be explain by localised vasoconstriction induced by the cooler temperature (Eston and Peters 1999) of CWI condition. Further, this reduced diVusion rate may assist in reducing acute inXammation from muscle damage and immune activation (Coté et al 1988;Stacey et al 2010). In turn, the reduced inXammation can reduce pain, swelling and the loss of force generation that is also often associated with the inXammatory process (Goodall and Howatson 2008;Smith 1991).…”
Section: Doms (Cm)mentioning
confidence: 96%
“…Bleakley and Costello (2013) reported some concern regarding the return to exercise after cooling and advised more careful use of cryotherapy before activities that demand good sensory-motor control in order to protect the physical integrity of the athlete. Bleakley and Costello (2013) also referred to a growing trend in the application of cold prior to exercise; however, these authors suggested that the benefits of its use should compensate for any deleterious physiological effect, as it is associated with a decrease in nerve conduction velocity (Herrera, Sandoval, Camargo, & Salvini, 2011) and muscle contraction (Bleakley et al, 2007) and changes in training and physical performance (Stacey, Gibala, Ginis, & Timmnos, 2010). In contrast, no changes were observed after cooling in the joint proprioception function (Costello, Algar, & Donnelly, 2012), balance (Rupp, Herman, Hertel, & Saliba, 2012) or in the EMG response (Berg, Hart, Palmieri-Smith, Cross, & Ingersoll, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…In athletes, several techniques have been proposed to achieve this result. Of these, active recovery, 8,9 contrast water therapy, 10 compression garments, 11 low-level laser therapy, 12 and lowfrequency electromyostimulation 13 have been investigated and compared with passive recovery (PAS). 6,14 The results of these studies provide no definitive consensus on the ability to improve explosive strength and anaerobic capacity performance or clear muscle damage markers after exercise.…”
mentioning
confidence: 99%